Diagnostic Consideration for Sinonasal Wegener's Granulomatosis Clinically Mistaken for Carcinoma. (9th September 2013) - La Rosa, Cristina; Emmanuele, Carmela; Tranchina, Maria Grazia; Ippolito, Massimo; Cosentino, Sebastiano; Saita, Vincenzo; Improta, Giuseppina; Fraggetta, Filippo
Abstract : We report a case of Wegener's granulomatosis clinically mistaken for carcinoma in a 21-year-old girl presenting with an ulcerated mass of the nasopharynx associated with enlarged laterocervical nodes. The lesion was clinically suspected as malignant on the basis of clinical and radiological findings (namely, computed tomography scan and positron emission tomography). However, multiple biopsies were not conclusive for malignancy showing histological change suggestive of Wegener's granulomatosis. A serum determination of cANCA supported the diagnosis of Wegener's granulomatosis. Clinical findings and image studies suggested an erroneous diagnosis of malignancy whereas a definitive diagnosis of Wegener's granulomatosis was achieved only after repeated biopsies thus leading to a correct therapeutic approach. The Wegener granulomatosis must be added to the list of the differential diagnoses of the masses of the nasopharynx associated with or without enlarged laterocervical nodes.